A New Secretory Peptide of Natriuretic Peptide Family, Osteocrin, Suppresses the Progression of Congestive Heart Failure After Myocardial Infarction. Issue 5 (2nd March 2018) - Miyazaki, Takahiro; Otani, Kentaro; Chiba, Ayano; Nishimura, Hirohito; Tokudome, Takeshi; Takano-Watanabe, Haruko; Matsuo, Ayaka; Ishikawa, Hiroyuki; Shimamoto, Keiko; Fukui, Hajime; Kanai, Yugo; Yasoda, Akihiro; et al.
Abstract : Rationale: : An increase of severe ischemic heart diseases results in an increase of the patients with congestive heart failure (CHF). Therefore, new therapies are expected in addition to recanalization of coronary arteries. Previous clinical trials using natriuretic peptides (NPs) prove the improvement of CHF by NPs. Objective: : We aimed at investigating whether OSTN (osteocrin) peptide potentially functioning as an NPR (NP clearance receptor) 3-blocking peptide can be used as a new therapeutic peptide for treating CHF after myocardial infarction (MI) using animal models. Methods and Results: : We examined the effect of OSTN on circulation using 2 mouse models; the continuous intravenous infusion of OSTN after MI and the OSTN-transgenic (Tg) mice with MI. In vitro studies revealed that OSTN competitively bound to NPR3 with atrial NP. In both OSTN–continuous intravenous infusion model and OSTN-Tg model, acute inflammation within the first week after MI was reduced. Moreover, both models showed the improvement of prognosis at 28 days after MI by OSTN. Consistent with the in vitro study binding of OSTN to NPR3, the OSTN-Tg exhibited an increased plasma atrial NP and C-type NP, which might result in the improvement of CHF after MI as indicated by the reduced weight of hearts and lungs and by the reduced fibrosis. Conclusions: : OSTN might suppress the worsening of CHF after MI by inhibiting clearance of NP family peptides. Abstract : Supplemental Digital Content is available in the text.